Variations of pulse and blood pressure in men at sea level and in the Andean highlands - Alfaro Alvarez, Raúl D. (1951)
The purpose of this work is the comparative study of ways to react to the same stimulus tests, man's height and sea level; adding and unpretentious to the valuable work of the Peruvian school which has been studying the problem of the physiology of the Andes for several decades.